Clinical characteristics and outcome in patients with combined diabetic ketoacidosis and hyperosmolar hyperglycemic state associated with COVID-19: A retrospective, hospital-based observational case series - Chan, Kok Hoe (Diabetes Res Clin Pract, 2020)
AIM: One of the risk factors for poor outcome with SARS-CoV-2 infection is diabetes mellitus; diabetic ketoacidosis (DKA) and hyperosmolar hyperglycemic state (HHS) are the most serious complications of diabetes mellitus. We aimed to explore the clinical characteristics and outcomes of COVID-19 patients presenting with combined DKA/HHS to our institution. METHODS: A retrospective, hospital based observation case series was performed on patients with SARS-CoV-2 admitted to Intensive Care Unit between 3/20/2020 and 4/20/2020. Inclusion criteria were: (1) Blood Glucose >250 mg/dL; (2) Serum bicarbonate <18 mmol/L; (3) Anion Gap >10; (4) serum pH <7.3; (5) ketonemia or ketonuria; (6) effective/calculated plasma osmolality >304 mOsm/kg and (7) positive SARS-CoV-2 RT-PCR. RESULTS: We reported 6 patients who presented during this period with combined DKA/HHS. Their median age was 50 years, all males, three Hispanic, and three African American. Hispanic patients, had more severe acidosis, and multiple comorbidities, with a higher mortality. The striking feature was that combined DKA/HHS was the initial presentation for COVID-19 for most of the cases. DISCUSSION: Our observational retrospective case series shows that diabetic patients are at risk of developing combined DKA/ HHS associated with COVID-19 and a substantial mortality. To our knowledge, we are first to report the clinical characteristics and outcome in this group of patients.